Pemeriksaan Ultrasonografi Hepar menjadi Pemeriksaan Penunjang yang Tepat untuk Diagnosa Hepatitis - Dimas Maulana Anshori; Nursama Heru; Gando Sari; Helwini Istiqomah (Poltekkes Kemenkes Jakarta III, 2019)
Hepatitis is inflammation of the liver due to viral or alcohol infection. Hepatitis can cause death and the case always increases every year both in Indonesia and the world. The aim of this study is to describe and evaluate the management of examination such as patient preparation procedure, tool preparation, patient position, transducer placement, transducer used, and ultrasound image of hepatitis. This research was conducted by qualitative descriptive method. The population is all patients who perform liver ultrasound examination at RSUD Cengkareng Jakarta. The samples used were patients who performed liver ultrasound examination with clinical hepatitis. The number of samples used is 2 patients. After being analyzed and observed, ultrasonography is an accurate and accurate examination of the hepatitis case. Additional scripting techniques are sometimes required in certain cases to make the results more optimal. Based on this research, it can be expected that ultrasound modalities can be used as an appropriate supporting tool in establishing clinical hepatitis with accurate, fast, cheap and safe results.